2020
DOI: 10.1038/s41598-020-76807-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new cell line from ornamental fish Amphiprion ocellaris (Cuvier, 1830) and its susceptibility to nervous necrosis virus

Abstract: Amphiprion ocellaris (ocellaris clownfish) is one of the most commercially important marine ornamental fish. A cell line designated as OCF was developed for the first time from the caudal fin of this fish species. The cell line was maintained in Leibovitz’s—15 medium supplemented with 15% FBS (Fetal Bovine Serum) and was successfully subcultured up to 34 passages. The cell line was authenticated by sequencing mitochondrial cytochrome C oxidase subunit I (COI) and 16S rRNA genes. The growth rate of the OCF cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…27,47 cryopreservation was demonstrated, and found to be higher than 80%, which is consistent with previous studies. 15,34,36 The cell viability obtained in the present study was similar to that reported by Ishak Ahmed et al 37 (85-90% recovery).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…27,47 cryopreservation was demonstrated, and found to be higher than 80%, which is consistent with previous studies. 15,34,36 The cell viability obtained in the present study was similar to that reported by Ishak Ahmed et al 37 (85-90% recovery).…”
Section: Discussionsupporting
confidence: 91%
“…The morphology presented by both cell lines was fibroblastic, with no irregularities becoming evident during this time. Yashwant et al 34 reported similar results when developing gill, liver and skin cell lines from fish.…”
Section: Discussionmentioning
confidence: 71%
“…The cox I gene was used as DNA barcodes for the authentication of 67 cell lines [ 20 ]. Similarly, many fish cell lines have been DNA barcoded using cox I [ 21 23 ]. Cell line repositories like DSMZ, ATCC use DNA barcoding as a standard method for cell line identification.…”
Section: Cell Line Characterizationmentioning
confidence: 99%
“…SISK and SISS cell lines developed from the kidney and spleen of Lates calcarifer respectively and SIGE cell line developed from the eye of Epinephelus coioides showed their ability to propagate a nodavirus strain [ 32 ]. Yashwanth et al reported the susceptibility of the OCF cell line to NNV [ 23 ]. SSN-1 cell line supported the replication of snakehead fish vesiculovirus (SHVV) which causes great economic loss in fish culture in East Asian countries [ 33 ].…”
Section: Fish Health Managementmentioning
confidence: 99%
“…In this study, we deal with partial fins cut from a fish’s body. Cultured fin tissues cut from fish bodies are known to show explants around the tissues in a culture flask 22 , 23 . Therefore, we investigated the cell variations that have experienced the regeneration process, including the differentiation potential if the cells have dedifferentiated.…”
Section: Introductionmentioning
confidence: 99%